1996
DOI: 10.2307/4002593
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Clipping on Root Systems of 3 Grasses Species in Tunisia

Abstract: The study concerns the impact of herbivory on the root systems of 3 perennial grasses, huffelgrass (Cenchnrs ctiti), digitgrass (Digitaria commutata) and needlegrass (Stipa lagascae), growing in the arid zones of Tunisia. The study simulated animals feeding of the grasses by affecting cuttings at various times throughout the spring growing period. The following effects on the root systems of the grasses were observed.When there is continual overgazing (simulated by cutting all sprouts down the ground level-alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 2 publications
0
21
0
2
Order By: Relevance
“…A relação inversa dos pares MS x RP2 e MS x RP3 evidenciou que com o aumento da RP houve diminuição da MS, proporcionada pelo aumento da compactação do solo na camada de 0,10-0,30 m de profundidade e, portanto, provavelmente pelas condições adversas ao crescimento radicular, uma vez que as raízes da braquiária apresentam maiores concentrações nas camadas mais profundas, se não forem superpastejadas. Assim, a relação inversa da MS x PT3 (r = -0,205*) e a direta entre MS x DS3 (r = 0,204*), provavelmente, podem ser atribuídas ao maior contato solo/raiz, com maior eficiência de absorção de água e nutrientes, incrementando a MS. Chaieb et al (1996), trabalhando com o capim Cenchrus cilliaris, demonstraram, no caso de dois a três cortes (simulação de pastejo leve), que o seu sistema radicular permaneceu superficial, com cerca de 58 a 67 % das raízes localizadas nos primeiros 15 cm da camada superficial de solo. No entanto, para as gramíneas Digitaria commutata e Stipa lagascae houve aprofundamento das raízes, localizando-se 68 a 86 % delas a 30 cm de profundidade.…”
Section: Resultsunclassified
“…A relação inversa dos pares MS x RP2 e MS x RP3 evidenciou que com o aumento da RP houve diminuição da MS, proporcionada pelo aumento da compactação do solo na camada de 0,10-0,30 m de profundidade e, portanto, provavelmente pelas condições adversas ao crescimento radicular, uma vez que as raízes da braquiária apresentam maiores concentrações nas camadas mais profundas, se não forem superpastejadas. Assim, a relação inversa da MS x PT3 (r = -0,205*) e a direta entre MS x DS3 (r = 0,204*), provavelmente, podem ser atribuídas ao maior contato solo/raiz, com maior eficiência de absorção de água e nutrientes, incrementando a MS. Chaieb et al (1996), trabalhando com o capim Cenchrus cilliaris, demonstraram, no caso de dois a três cortes (simulação de pastejo leve), que o seu sistema radicular permaneceu superficial, com cerca de 58 a 67 % das raízes localizadas nos primeiros 15 cm da camada superficial de solo. No entanto, para as gramíneas Digitaria commutata e Stipa lagascae houve aprofundamento das raízes, localizando-se 68 a 86 % delas a 30 cm de profundidade.…”
Section: Resultsunclassified
“…The buffel grass has features that make it competitive to survive in arid and semiarid conditions, among them a deep root system which according to Halvorson & Guertin (2003) allows access the water supply faster and for longer time than the native species. Thus, it is important to observe the development of the root system to develop management strategies of buffel grass (Chaieb et al, 1996;Mnif & Chaieb, 2009). In this study, it was observed that increasing doses of P promoted the linear development of the root system, showing the competitive strategy and adaptive of the specie.…”
Section: Resultsmentioning
confidence: 81%
“…Despite its wide distribution, the expansion of overgrazing associated with the severity of climatic factors in arid ecosystems has led to a continuous thinning of stands and the threat of extinction of this species throughout its natural area of occurrence (Chaieb et al 1996;Whitford 2002). Considering the ecological interest offered by C. ciliaris: drought tolerance (Bhatt et al 2007; De La Barrera and Castellanos 2007;Kharrat-Souissi et al 2012a), high fodder production and nutritive value to livestock (Kharrat-Souissi et al 2010;Arshadullah et al 2011), rapid regeneration in response to rainfall (Bose and Balakarishnan 2001), tolerance of heavy grazing (M'seddi et al 2004a) and soil stabilisation abilities because of a deep root system (Chaieb et al 1996;Mnif and Chaieb 2009), the persistence of this species in its native range in arid ecosystems is a crucial factor for restoration ecology of degraded arid rangelands.…”
Section: Adaptive Characteristicsmentioning
confidence: 99%
“…Despite its wide distribution, the expansion of overgrazing associated with the severity of climatic factors in arid ecosystems has led to a continuous thinning of stands and the threat of extinction of this species throughout its natural area of occurrence (Chaieb et al 1996;Whitford 2002). Considering the ecological interest offered by C. ciliaris: drought tolerance (Bhatt et al 2007; De La Barrera and Castellanos 2007;Kharrat-Souissi et al 2012a), high fodder production and nutritive value to livestock (Kharrat-Souissi et al 2010;Arshadullah et al 2011), rapid regeneration in response to rainfall (Bose and Balakarishnan 2001), tolerance of heavy grazing (M'seddi et al 2004a) and soil stabilisation abilities because of a deep root system (Chaieb et al 1996;Mnif and Chaieb 2009), the persistence of this species in its native range in arid ecosystems is a crucial factor for restoration ecology of degraded arid rangelands. For these reasons, C. ciliaris has been the subject of numerous applied studies, which have focussed on its phenotypic polymorphism, its ecological significance (M'seddi et al 2002;Arshad et al 2007;Jorge et al 2008;Visser et al 2008;Kharrat-Souissi et al 2010;Arshadullah et al 2011), resistance to drought (Mansoor et al 2002;Mnif and Chaieb 2010;Kharrat-Souissi et al 2012a), biological invasion capacity (Friedel et al 1996;Franklin et al 2006;GutierrezOzuna et al 2009;Marshall et al 2012) and its genotypic diversity (Nisar et al 2010;Al-Soqeer 2011;Kharrat-Souissi et al 2011).…”
Section: Adaptive Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation